Estudo de parâmetros físico-químicos de efluente e dos recalques de resíduos sólidos urbanos em ensaios realizados em lisímetros - Ribeiro, Eliana Dantas (2024)
The generation of landfill leachate has polluting consequences for the soil and water bodies, and this is one of the major motivating factors for the in-depth study of the characteristics of the leachate generated. Physico-chemical leachate parameters such as chemical oxygen demand (COD), electrical conductivity, pH, ions, etc. are useful for investigating the biodegradation phases of municipal solid waste (MSW). Given that biodegradation is responsible for a large part of the settlements that occur in MSW landfills, it is important to monitor the biodegradation phases in which the mass of waste is found. These parameters do not behave individually, as they are interconnected. The use of field lysimeters, exposed to environmental conditions, makes it possible to simulate the biodegradation behavior of MSW. In this work, three lysimeters were built: lysimeter L1 (containing MSW), lysimeter L2 (with leachate recirculation and containing organic solid waste - OSR), lysimeter L3 (without leachate recirculation and containing OSR), covered by a layer of intermediate cover from landfills in the state of Ceará. In lysimeter L3, without recirculation, there was a decrease in COD compared to lysimeter L2 with recirculated slurry. The recirculation of leachate contributed to greater settlements and to making the leachate more concentrated with salts such as chlorides, which directly influenced the increase in electrical conductivity. The Lysimeter L1 (MSW) showed lower COD values than lysimeters L2 and L3. The settlements for the RSO lysimeters were greater than the settlements for the MSW lysimeter, where L1 (MSW) showed a settlement of 25 cm, L2 (RSO and with recirculation) 40 cm and L3 (RSO and without recirculation) 39 cm, over a 6-month monitoring period. Although the adjustments to the Ling et al. (1998) model were close to the measured settlements over the majority of the monitoring period, it should be used with caution when forecasting long-term settlements. This model does not take into account the variables that influence biodegradation, such as pH, COD and the types of bacteria involved, and this may underestimate the settlements in the mass of waste. Lysimeter L1 (of MSW) at the end of 6 months of monitoring, was still in an initial aerobic phase of MSW gas generation. Lysimeter L2 (with recirculation), at the end of monitoring, had a pH lower than 5, indicating that it was in the acid anaerobic phase. In lysimeter L3 (without recirculation), anaerobic conditions were at an early stage at the end of monitoring, suggesting that it was in a process of transition from the aerobic to the anaerobic phase, and starting the acid phase in the last month of monitoring. The results indicate that the use of an intermediate cover layer in the construction period of a landfill influences the range of MSW biodegradation phases, as well as the physicochemical parameters of the leachate.